A Clinico-Pathological Study on Vatarakta w.s.r. to Gout and its Comparative Effect of Bodhivrikshya Kashaya and Bodhivrikshya Ghana Vati. - Chandrakar, Bedprakash; Singh, Vinod Chandra; Panda, Pradip Kumar; Panda, Sushmirekha (International Research Journal of Ayurveda & Yoga, 2022)
Vatarakta is the major example of Vatavyadhi, caused due to avarana pathology. The scenario of Vatarakta featuring sign & symptoms which can very well be correlated with Gouty Arthritis. The literature enlists a number of formulation in the management of Vatarakta. An additional cavernous revise was indispensable to bring out the precise outcome of these products. Keeping these visions in mind, the particular comparative study was performed with Bodhivrikshya Kashaya and Bodhivrikshya Ghana Vati, which are explained in the same context. This is a single-blind comparative clinical study with a pre test and post-test design, wherein a minimum of 30 patients of either sex, suffering from Vatarakta, in an age limit of 20 to 50 years with symptoms like sandhishoola (joint pain), sotha (swelling), kandu (itching), daha (burning sensation), twakvaivarna (discolouration), sparshaasahatwa (tenderness), sphurana(twitching)and serum uric acid value more than 6.8mg/dl were selected and randomly categorized into two groups. The 15 patients of group A were treated with oral administration of Bodhivrikshya Kashaya 25ml twice day and the group B patients with Bodhivrikshya Ghana Vati 2tab(1tab-500mg) thrice daily with anupana of Madhu. The therapeutic effect of the treatment was assessed in both the groups based on specific subjective and objective parameters. The results obtained were analyzed statistically in both the groups and the comparative effect was assessed using the unpaired “t”-test. In both the groups, a statistically significant improvement was observed in all the criteria of assessment. The outcome of the study revealed an identical therapeutic efficacy of Bodhivrikshya Kashaya and Bodhivrikshya Ghana Vati in Vatarakta but Bodhivrikshya Kashaya have shown more than Bodhivrikshya Ghana Vati. No Adverse effect was noticed during clinical trial in both groups.